2004
DOI: 10.1210/en.2003-0774
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cyclic-ADP-Ribose-Signaling Pathway in Oxytocin-Induced Ca2+ Transients in Human Myometrium Cells

Abstract: Human myometrial contraction plays a fundamental role in labor. Dysfunction of uterine contraction is an important cause of labor progression failure. Although the mechanisms controlling uterine contraction are not completely understood, intracellular Ca2+ mobilization plays an important role during uterine contraction. Several mechanisms of intracellular Ca2+ mobilization are present in smooth muscle, but in the human uterus, only 1,4,5-trisphosphate-induced Ca2+ release has been studied extensively. Ryanodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 33 publications
6
63
0
Order By: Relevance
“…OT stimulation was dually controlled by IP 3 and cADPR, resembling human myometrium cells (Barata et al, 2004 antagonist delayed the initial peak. In contrast, the cADPR was largely responsible for the sustained Ca 2+ signal for up to 5 min because of blockade by the pretreatment of nerve endings with 8-bromo-cADPR, which was also mimicked by the PKC inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…OT stimulation was dually controlled by IP 3 and cADPR, resembling human myometrium cells (Barata et al, 2004 antagonist delayed the initial peak. In contrast, the cADPR was largely responsible for the sustained Ca 2+ signal for up to 5 min because of blockade by the pretreatment of nerve endings with 8-bromo-cADPR, which was also mimicked by the PKC inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that human smooth muscle cells utilize the CD38/cADPR pathway to modulate [Ca 2+ ]i transients during agonist stimulation (18). The components of this pathway are present and functional in myometrial, vascular and airway smooth muscle cells (18)(19)(20)(21)(22)(23)(24).…”
Section: Role Of Cadpr In Agonist-stimulated Ca 2+ Transientsmentioning
confidence: 98%
“…Human myometrial cells were isolated using techniques previously described (18). Briefly, the tissue was minced in Hanks' balanced salt solution (HBSS) containing 10 mM glucose and 10 mM HEPES, pH 7.4.…”
Section: Cell Preparationmentioning
confidence: 99%
“…TNF-a, another important inflammatory cytokine, was previously demonstrated to induce expression of CD38 in airway and myometrial smooth muscles (48,85). The pathophysiologic role of TNF-a is shown by the fact that it is found in high levels in bronchoalveolar lavage fluid and sputum of patients with asthma and chronic obstructive pulmonary disease (86,87).…”
Section: Inflammatory Cytokines and Cd38/cadpr-mediated Cellular Calcmentioning
confidence: 99%